Geographic variability in the gonadal development and sexual ontogeny of Hemigymnus, Cheilinus and Oxycheilinus wrasses among Indo‐Pacific coral reefs. Issue 4 (5th August 2021) - Lowe, Jake R.; Russ, Garry R.; Bucol, Abner A.; Abesamis, Rene A.; Choat, John H.
Abstract: Patterns of reproductive ontogeny in four species of coral reef wrasses (F: Labridae) Hemigymnus melapterus, Hemigymnus fasciatus, Cheilinus fasciatus and Oxycheilinus digramma were investigated. Populations of each species were sampled from two island groups of the central Great Barrier Reef (GBR), Australia, and from coral reefs in the central Philippines. These three sampling locations span 30° of latitude. The GBR and Philippine reefs experience biologically significant differences in water temperature, geography and human activity. The studied wrasses are effectively unfished in Australia but heavily fished in the Philippines. Gonad weights, histology and demographic data were obtained across the entire size and age range of H. melapterus, C. fasciatus and O. digramma from all locations. Analysis identified three processes of male recruitment: functional gonochorism and both forms of protogynous hermaphroditism, monandry and diandry. The expression of these distinct sexual ontogenies was locality dependent. Populations of H. melapterus, H. fasciatus, C. fasciatus and O. digramma on the GBR showed consistently uniform patterns of sexual ontogeny, with all species being exclusively monandric. H. melapterus, C. fasciatus and O. digramma in the Philippines displayed complex sexual ontogenies, with all species showing histological evidence of both diandry and functional gonochorism. Reproductive investment in gonadal tissue, and population sex structure, also differed between GBR and Philippine coral reefs. Philippine populations had substantially lower gonado‐somatic indices than populations on the GBR. Nonetheless, Philippine populations matured more rapidly and displayed a protracted timing of sex change over a large size and age range. Thus, mature females appeared earlier and persisted later into ontogeny in the Philippines than on GBR reefs. Protracted timing of sex change on Philippine reefs is likely linked to the presence of primary males in the population, which is known to reduce the strength of selection for mature females to undergo sex change and become male. Hypotheses based on social structure of fish populations, environmental factors and evolutionary history were developed to account for the different patterns of sexual ontogeny in the focal wrasses.